PENGARUH STRES KERJA DAN KEPUASAN TERHADAP KINERJA KARYAWAN MEDIS (Kasus Pada Karyawan Medis Rumah Sakit Azzahra – Ujungbatu) - Lilla Ilham; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research aims to determine the influence of job stress and job statistification towards employee’s preformance (case study Rumah Sakit Az-Azahra Ujungbatu). Job stress as variable X1, job statistification as variable X2 and employee’s preformance as variable Y.The research method in this research is quantitative method with SPSS programme, which the sample is the medic employee as much as 47 respondents. The sample in this research is 47 employees of Rumah Sakit Az-Azahra Ujungbatu Which is all of the population. The data is collected through the questionnaires.The results of this research concludes that the variable of job stress is significantly influential to employees perfoormance and the job statification is significantly influential to the employee’s performance, and job stree and job stratification are simultaneously influenctial to the employee’s performance.Keywords: job stress, job statistification, employee’s performance